Pengaruh Intensitas Terpaan Iklan Shopee di Televisi Terhadap Minat Beli Mahasiswa - Rifani Nur Hanifa; Ana Fitriana P.; Yanti Tayo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Singaperbangsa Karawang, 2018)
This study aims to find out how the intensity advertisement’s exposure influential on interest to purchase by students. This research uses quantitative approach with multiple linear regression analysis with support from Individual Difference Theory. Based on advertising exposure to buying interest then the theory used Individual Difference Theory. This theory assumes that differences among individuals are targeted by the mass media when they are buffeted so as to have a certain effect. The results of this study found that the intensity of exposure to shopee advertisements affected students' buying interest in terms of language, jingles and models in advertisements. The language in the advertisement has a very high influence of 57%.Keywords: Influence, Shopee Ads Force, Buy Interest